Avaliação das propriedades mecânicas do concreto com pó de pedra e agregados reciclados de concreto - Chaves, Francisco de Assis (Universidade Federal Rural do Semi-Árido, 2019)
Environmental issues have become a hot topic around the world. There is the desire to grow, at the same time, the concern with future generations. In this context, solutions to mitigate environmental impacts are increasingly being sought through research. The extraction of aggregates for concrete production and the inadequate disposal of construction waste has brought several damages to the environment. Thus, this research aimed to analyze the effects of the incorporation of two construction residues, crushing stone dust and recycled concrete aggregate, on the characteristics of concrete, with emphasis on the implications of the addition of this on their properties. mechanical. The stone dust was collected in a crusher in Encanto - RN, while the recycled concrete aggregate was produced by fractioning laboratory molded specimens. The dosage was made based on the ABCP / ACI method, and for this there was the characterization of the aggregates used, including the residues. The concretes were dosed to a characteristic strength of 25 MPa and 5 strokes were made: the reference, containing only natural aggregates, one with 10% stone dust as a substitute for fine aggregate, and the other three, with a fixed percentage of 10 % stone dust to replace sand, and 5%, 10% and 15% recycled concrete aggregate to replace coarse aggregate. Based on the absorption result of the recycled aggregate, it was decided to wet it before adding it to the mixture. For the technological control of the concrete, the tests of fresh specific mass, consistency, absorption at 28 days and compressive strength at 7, 21 and 28 days were performed. All traits were found to have higher than desired resistance, with the exception of 10% stone dust and 15% recycled aggregate, which was inconclusive. Therefore, the addition of residues in concretes proved to be very efficient options in replacing natural aggregates.
Keywords: Impactos ambientais; Resíduos da construção civil; Controle tecnológico do concreto; Resistência à compressão; Environmental impacts; Construction wastes; Technological control of concrete; Compressive strength; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA